A New Family of Wasps - Howard E. Evans (Psyche: A Journal of Entomology)
The classification of the aculeate Hymenoptera is considerably complicated by the existence of a number of small families of doubtful relationships, families such as the Plumariidae, Rhopalosomatidae, Sierolomorphidae, Sclerogibbidae, and Loboscelidiidae. To add still another family to this list is a dubious distinction, and to base such a family on twelve specimens may be considered a dubious procedure. Nevertheless these twelve specirnens present such an unusual array of structural features that they can scarcely be ignored. Although some of these features are clearly specializations, others are so very generalized, for Aculeata, that there can be little question that this family is a relict of a very ancient stock of wasps. These wasps have the habitus of certain Scolioidea, and probably the family should be placed in that superfamily. However, because of the 13-segmented antennae in the female and the lack of closed cells in the hind wings, the family will fall in the Bethyloidea in most classifications. The name of the type genus, Scolebythus, is meant to imply a sharing of certain characteristics of both these superfamilies of primitive Aculeata (scolbeing a prefix derived from Scolia, lebythus an anagram of Bethylus). Further discussion of the relationships of the family is deferred until after the descriptive material. In the description of the family, I have numbered the more significant characters so that these can be referred to more readily later on.